Use of intravenous immunoglobulin in neonates with haemolytic disease and immune thrombocytopenia - Marković-Sovtić, Gordana; Janković, Borisav; Rakonjac, Zorica; Martić, Jelena; Pejić, Katarina (Vojnosanitetski pregled, 2017)
Background/Aim. Intravenous immunoglobulin is a blood product made of human polyclonal immunoglobulin G. The mode of action of intravenous immunoglobulin is very complex. It is indicated in treatment of neonatal immune thrombocytopenia and haemolytic disease of the newborn. The aim of the study was to present our experience in the use of intravenous immunoglobulin in a group of term neonates. Methods. We analysed all relevant clinical and laboratory data of 23 neonates who recieved intravenous immunoglobulin during their hospitalization in Neonatal Intensive Care Unit of Mother and Child Health Care Institute over a five year period, from 2006. to 2010. Results. There were 11 patients with haemolytic disease of the newborn and 12 neonates with immune thrombocytopenia. All of them recieved 1–2 g/kg intravenous immunoglobulin in the course of their treatment. There was no adverse effects of intravenous immunoglobulin use. The use of intravenous immunoglobulin led to an increase in platelet number in thrombocytopenic patients, whereas in those with haemolytic disease serum bilirubin level decreased significantly, so that some patients whose bilirubin level was very close to the exchange transfusion criterion, avoided this procedure. Conclusion. The use of intravenous immunoglobulin was shown to be an effective treatment in reducing the need for exchange transfusion, duration of phototherapy and the length of hospital stay in neonates with haemolytic disease. When used in treatment of neonatal immune thrombocytopenia, it leads to an increase in the platelet number, thus decreasing the risk of serious complications of thrombocytopenia.